Status and Condition of Mangroves in Mangrove Ecosystem on Tongkeina Coast Bunaken National Park - Kolinug, Oscean; Sinjal, Chatrien A. L.; Kusen, Janny D.; Manengkey, Hermanto W.K.; Djamaaludin, Rignolda; Rumampuk, Natalie D.C. (Jurnal Ilmiah Platax, 2024)
Mangrove ecosystems are a typical type of vegetation found in tropical coastal areas. Mangrove vegetation generally thrives in gently sloping coastal areas near river mouths and beaches that are protected from wave forces. The mangrove forest ecosystem is a nursery ground for young fauna (juvenile stage) that will grow into adult individuals and is also a spawning ground for several animals and other aquatic biota such as birds, insects, snakes, shrimp, fish, and shellfish. This research was conducted at 3 different points. The results showed that there were 6 types of mangroves at the three stations including Soneratia alba, S. ovata, Rhizophora apiculata, R. stylosa, Avicennia marina, and A. alba. High diversity (H') is found at Station 2 and Station 3 at 0.4 and Station 1 at 0.2 with a Dominance value (D) Medium at Station 1 at 0.37 while Stations 2 and 3 at 0.27 and 0.28 are categorized as low, Uniformity (e) at all stations is high with values of 0.74, 0.89 and 0.70, absolute density is highest at Station-1 and Station-2 with a value of 0.10%, and at Station-3 the lowest Absolute Density is 0.06%, Community Similarity (IS) mangrove species at all three locations are the same because they still cover the same location in the intertidal area. Keywords: Community structure, Mangrove, Tongkeina. Abstrak Ekosistem mangrove merupakan tipe vegetasi khas yang terdapat di daerah pantai tropis. Vegetasi mangrove umumnya tumbuh subur di daerah pantai yang landai di dekat muara sungai dan pantai yang terlindung dari kekuatan gelombang. Ekosistem hutan mangrove merupakan daerah asuhan (nursery ground) fauna-fauna muda (juvenile stage) yang akan bertumbuh kembang menjadi individu dewasa dan juga merupakan daerah pemijahan (spawning ground) beberapa satwa dan biota perairan lain seperti burung, serangga, ular, udang, ikan dan kerang-kerangan.Penelitian ini dilakukan di 3 titik yang berbeda. Hasil penelitian menunjukan terdapat 6 jenis mangrove pada ketiga stasiun di antaranya Soneratia alba, S. ovata, Rhizophora apiculata, R. stylosa, Avicennia marina  dan A. alba. Keanekaragaman tinggi (H’) terdapat pada Stasiun 2 dan Stasiun 3 0,4 serta Stasiun 1 0,2 dengan nilai Dominansi (D) dikategorikan sedang pada Stasiun 1 0,37 sedangkan Stasiun 2 dan 3 0,27 dan 0,28 dikategorikan rendah, Keseragaman (e) pada semua stasiun tinggi dengan nilai 0,74, 0,89 dan 0,70, kepadatan mutlak tertinggi pada Stasiun-1 dan Stasiun-2 dengan nilai 0,10%, dan pada Stasiun-3 Kepadatan Mutlak terendah yaitu 0,06%, Kesamaan Komunitas (IS) jenis bakau pada ketiga lokasi sama karena masih mencakup satu lokasi yang sama di daerah intertaidal. Kata kunci : Struktur komunitas, Mangrove, Tongkeina.